Cell changes during the re-induction of desiccation tolerance in germinated seeds of Sesbania virgata (Cav.) Pers. - Tathiana Elisa Masetto; Ana Carla Resende Fraiz; José Márcio Rocha Faria (Journal of Seed Science, 2016)
Abstract During germination, orthodox seeds lose their ability to tolerate desiccation resembling recalcitrant seeds. This research aimed to investigate the cell changes during the re-induction of the desiccation tolerance (DT) in Sesbania virgata germinated seeds with 1, 3 and 5 mm long radicles. To re-establish DT, germinated seeds were incubated for 72 h in polyethylene glycol (PEG, -2.04 MPa) before dehydration in silica gel (at 10% moisture content) followed by rehydration. Cell viability was assessed through TUNEL test in dry radicles and transmission electron microscopy in both fresh and dry radicles. The positive-TUNEL confirmed the DNA degradation, through the green fluorescence of the cell nuclei from 5 mm radicle length and the ultra structural evaluations detected loss of cellular content integrity in 3 and 5 mm cell radicles that did not survive dehydration to 10%.